Fine Needle Aspiration Cytology Study of Tuberculous Lymphadenitis with Ancillary Diagnostic Procedures- Analytical Study from A Resource Limited Domicile of East Coastal Region: Life Sciences-Nursing - K, Anandraj vaithy; E, Keerthika Sri; .K, S. Shanmugasamy; S, Sowmya (International Journal of Life Science and Pharma Research, 2023)
Tuberculosis remains one of the major causes of morbidity and mortality in developing countries like India despite intense health campaigning and Government Programmes. Tuberculous lymphadenitis is the most common extrapulmonary manifestation of tuberculosis; the incidence is still on a higher margin, especially in resource-poor areas, which often goes unnoticed and remains to date as a diagnostic challenge to Pathologists. The novel aim was to advocate the best method for early and correct diagnosis of tuberculous lymphadenitis to initiate early appropriate treatment.: In the prospective study conducted in our institute, Puducherry, a total number of 145 cases clinically suspected of tuberculous lymphadenopathy were included, and patients with neoplastic lesions were excluded from this study. The lymph node aspirate collected was analyzed for tuberculous cytomorphological changes using routine cytological stains and correlated observations with the results of various ancillary diagnostic procedures. Among 145 cases studied, 25 aspirates showed classical tuberculous patterns on cytomorphology, correlating well with histopathology (100%), PCR (100%), and culture (92%), respectively. In the rest of the 120 cases carrying non-tuberculous patterns on cytology, further exploration by ancillary diagnostic procedures revealed tuberculosis in 35 cases on histopathology, which PCR confirms in 25 available cases and culture study.FNAC results in adjunction with histopathology, and PCR showed increased reliability and pick-up rate in diagnosing atypical presentations of tuberculous lymphadenitis. Therefore, the PCR procedure of even conventional method should be widely employed in endemic areas of resource-poor regions.